Novel Climate Smart Water and Nutrient Conservation Technologies for Optimizing Productivity of Marginal Coarse-Textured Soils - Olupot, Giregon; Smucker, A. J. M.; Kalyango, S.; Opolot, Emmanuel; Orum, Boniface; Musinguzi, Patrick; Twaha, A. B.; Singh, B. R. (Cham: Springer International Publishing, 2021)
Water and nutrients are the two most limiting factors to productivity especially under rain-fed agriculture (RFA) in moist, semi-arid and arid regions. The dramatic doubling in yields and production from the 1960s to the 1990s, were through rapid expansion into irrigated prime land (FAO 1986; Higgins et al. 1988; Fischer et al. 2010; FAO 2011a). The prospects of further expanding agriculture into uncultivated lands and, into lakes, rivers, swamps and marshes (as alternative sources of water) are bleak. Withdrawal and consumption of these resources have already surpassed the Earth’s supply and regeneration capacity (Fischer et al. 2010). Higgins et al. (1988) estimated water requirements for food intake (in cereal equivalents) of 300 kg cap−1 yr−1 at 600 to 3,000 m3 cap−1 yr−1 (1 m3 = 1,000 L). Out of the Earth’s renewable water resources totaling 42,000 km3 annually, 3,900 km−3 is already being abstracted from rivers and aquifers distributed as 70% (2,730 km3) irrigation, 19% (741 km3) industrial and 11% (429 km3) municipal uses (Fischer et al. 2010; FAO 2011a). Water withdrawals exceeding 20% exert substantial pressure on renewable freshwater resources and those exceeding 40% are considered critical (Fischer et al. 2010; FAO 2011a). Withdrawals in the Middle East, North Africa and Central Asia already exceed critical thresholds with demand outstripping supply, posing serious threats to ecological functions of the water resources (FAO 2011a; Fischer et al. 2010). China, India, USA, Russia, Germany and Pakistan dominate irrigated area globally (Higgins et al. 1988; Fischer et al. 2010; FAO 2011a).
Keywords: Novel Climate Smart Water; Nutrient Conservation Technologies; Marginal Coarse-Textured Soils